Multilingualism and Local Literacy Practices in Ethiopia: Language contact in regulated and unregulated spaces - Lanza, Elizabeth; Woldemariam , Hirut (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The study of the linguistic landscape has provided a new dimension to theories and issues related to multilingualism, including language policy. In this growing field of inquiry, however, not enough attention has been given to the linguistic landscape in sites in the Global South. Since one of the aims of literacy studies is to reveal the variety and social patternings of practices, there is a need to compare linguistic landscape data with other various textual materials. In this article, we present linguistic landscape data from two federal regional capitals in Ethiopia that demonstrate multilingual language use. We also compare the linguistic contact patterns with those found in schoolbooks used in the same region. Such a comparison involves language use in unregulated as well as in regulated spaces (see Sebba 2009). Regional ethnically based languages are now being used in new arenas, including the linguistic landscape and education because of a new language policy promoting the use and development of regional languages. The two regional capitals provide privileged sites for examining the products of local literacy practices, involving values, attitudes, ideologies, and social relationships. We discuss the results in light of various ideologies and argue for the speaker-writer’s active mobilisation of multilingual resources in new language arenas.